Вы находитесь на странице: 1из 6

Quadratic Expressions

11 and Equations

Paper 2 10. 4x2 − 1


= (2x)2 − 12
1. (x + 4)(x + 2) = (2x − 1)(2x + 1)

= (x)(x) + (x)(2) + (4)(x) + (4)(2) 11. x2 − 2x − 3


= x2 + 2x + 4x + 8 = (x − 3)(x + 1)
= x2 + 6x + 8
x −3 −3x
2. (x − 1)(x + 3) x 1 x +
= (x)(x) + (x)(3) + (−1)(x) + (−1)(3) x 2
−3 −2x
= x2 + 3x − x − 3
= x2 + 2x − 3
12. m2 + 5m − 14
3. (2x − 3)(x + 4) = (m + 7)(m − 2)
= (2x)(x) + (2x)(4) + (−3)(x) + (−3)(4) m 7 7m
= 2x2 + 8x − 3x − 12 m –2 –2m +
= 2x2 + 5x − 12
m 2
–14 5m
4. (3x − 5)(x − 2)
= (3x)(x) + (3x)(−2) + (−5)(x) + (−5)(−2)
= 3x2 − 6x − 5x + 10 13. p2 − 6p + 8
= 3x2 − 11x + 10 = (p − 4)(p − 2)
p –4 –4p
5. (x + 5)(4x − 1) p –2 –2p +
= (x)(4x) + (x)(−1) + (5)(4x) + (5)(−1)
p 2
8 –6p
= 4x2 − x + 20x − 5
= 4x2 + 19x − 5
14. h2 + 8h + 15
6. 2x2 + 4 = 2(x2 + 2) = (h + 5)(h + 3)
h 5 5h
7. x2 − 3x = x(x − 3)
h 3 3h +
8. x − 1
2 h 2
15 8h
= x2 − 12
= (x − 1)(x + 1)
15. 2y2 + 5y − 3
9. x2 − 9 = (2y − 1)(y + 3)
= x2 − 32 2y –1 –y
= (x − 3)(x + 3)
y 3 6y +
2y 2
–3 5y

1 © Penerbitan Pelangi Sdn. Bhd.


  Mathematics  SPM  Chapter 11

16. 2x2 + x − 15 2n2 + 5n


25. –––––––– = 2
= (2x − 5)(x + 3) 1+n
2n + 5n = 2(1 + n)
2
2x –5 –5x
2n2 + 5n = 2 + 2n
x 3 6x + 2n2 + 5n − 2 − 2n = 0
2x2 –15 x 2n2 + 3n − 2 = 0

26. x2 − 4x = 0
17. 3x − 5x − 12
2 x(x − 4) = 0
= (3x + 4)(x − 3) x = 0 or x − 4 = 0
x = 4
3x 4 4x
Hence, x = 0 or x = 4.
x –3 –9x +
3x 2
–12 –5x 27. 2t2 = 3t
2t2 − 3t = 0
t(2t − 3) = 0
18. 3p2 − 11p + 6 t = 0 or 2t − 3 = 0
= (3p − 2)(p − 3) 2t = 3
t = — 3
3p –2 –2p
2
p –3 –9p + 3.
Hence, t = 0 or t = —
3p2 6 –11p 2

28. (p − 2)(p + 3) = 0
p − 2 = 0 or p + 3 = 0
19. x2 = 4x − 3 p = 2 p = −3
x − 4x + 3 = 0
2

Hence, p = 2 or p = −3.

20. 2h2 + 3h = 2h + 15 29. y2 − 3y − 4 = 0


2h2 + 3h − 2h − 15 = 0 (y − 4)(y + 1) = 0
2h2 + h − 15 = 0 y – 4 –4y
y 1 y +
21. x(x + 1) = 12
x2 + x = 12 y 2
– 4 –3y
x2 + x − 12 = 0
y − 4 = 0 or y + 1 = 0
y = 4 y = −1

22. p2 = 4(p − 2) Hence, y = 4 or y = −1.


= 4p − 8
p2 − 4p + 8 = 0 30. 2k2 − 9k − 5 = 0
(2k + 1)(k − 5) = 0
2k 1 k
23. 3y2 = 2(y − 1) + 7
k –5 –10k +
3y2 = 2y − 2 + 7
3y2 − 2y − 5 = 0 2k2 –5 –9k

2k + 1 = 0 or k − 5 = 0
2m − 5 = 3m
2 2k = −1 k = 5
24. –––––––
3 k = − — 1
2m2 − 5 = 3 × 3m 2
2m2 − 5 = 9m 1 or k = 5.
Hence, k = − —
2m2 − 9m − 5 = 0 2

© Penerbitan Pelangi Sdn. Bhd. 2


 Mathematics  SPM  Chapter 11 

4. 5x2 + 11x = 2(3 – x)


5x2 + 11x = 6 – 2x
5x2 + 11x + 2x – 6 = 0
Paper 2 5x2 + 13x − 6 = 0
(5x – 2)(x + 3) = 0
1. x(2x – 1) = 10
2x2 – x = 10 5x –2 –2x
2x2 – x − 10 = 0 x 3 15x +
(2x − 5)(x + 2) = 0
5x2 –6 13x
2x –5 –5x
x 2 4x + 5x – 2 = 0 or x + 3 = 0
2
2x2 –10 –x x = x = –3
5
2x − 5 = 0 or x + 2 = 0 2
Hence, x = or x = –3.
2x = 5 x = −2 5
x = — 5
2 5. 2h2 – 8 = 3h
–––––––
5
Hence, x = — 5 or x = −2. 2h2 − 8 = 5 × 3h
2
2h2 − 8 = 15h
2h2 − 15h − 8 = 0
2.
3x(3x + 2) – 1 = 6x (2h + 1)(h − 8) = 0
9x2 + 6x – 1 = 6x
9x2 + 6x – 6x = 1 2h 1 h
9x2 = 1 h –8 –16h +
1 2h 2
–8 –15h
x =
9
1 1 2h + 1 = 0 or h − 8 = 0
x=  or x = – 
3 3 2h = −1 h = 8
h = − — 1
3p2 − 4p 2
3. –––––––– = 5
2−p 1 or h = 8.
Hence, h = − —
3p2 − 4p = 5(2 − p) 2
3p2 − 4p = 10 − 5p
3p2 − 4p − 10 + 5p = 0 5x + 15 = x – 1
3p2 + p − 10 = 0 6.
2x
(3p − 5)(p + 2) = 0 5x + 15 = 2x(x – 1)
3p –5 –5p 5x + 15 = 2x2 – 2x
0 = 2x2 – 2x – 5x – 15
p 2 6p + 2x2 – 7x – 15 = 0
3p 2
–10 p (2x + 3)(x – 5) = 0
2x 3 3x
3p − 5 = 0 or p + 2 = 0
3p = 5 p = −2 x –5 –10x +
5 2x2 –15 –7x
p = —
3
5 or p = −2. 2x + 3 = 0 or x − 5 = 0
Hence, p = — 2x = −3 x = 5
3
x = − — 3
2
3 or x = 5.
Hence, x = − —
2

3 © Penerbitan Pelangi Sdn. Bhd.


  Mathematics  SPM  Chapter 11

3x(x − 2) 2. n2 = 4(n + 3)
7. –––––––– = 2−x
4 n2 = 4n + 12
3x(x − 2) = 4(2 − x) n2 − 4n − 12 = 0
3x2 − 6x = 8 − 4x (n − 6)(n + 2) = 0
3x2 − 6x − 8 + 4x = 0
n –6 –6n
3x2 − 2x − 8 = 0
(3x + 4)(x − 2) = 0 n 2 2n +
3x 4 4x n 2
–12 –4n
x –2 –6x + n − 6 = 0 or n + 2 = 0
3x 2
–8 –2x n = 6 n = −2
Hence, n = 6 or n = −2.
3x + 4 = 0 or x−2=0
3x = −4 x = 2
x = − — 4 3. 2x2 = 7x − 3
3 2x2 − 7x + 3 = 0
4 or x = 2.
Hence, x = − — (2x − 1)(x − 3) = 0
3 2x –1 –x
x –3 –6x +
8. x2 – 2x – 11 = 3(x + 1) 2x2 3 –7x
x2 – 2x – 11 = 3x + 3
x2 – 2x – 3x – 11 – 3 = 0 2x − 1 = 0 or x − 3 = 0
x2 – 5x – 14 = 0 2x = 1 x = 3
(x – 7)(x + 2) = 0 1
x = —
x –7 –7x 2
1 or x = 3.
Hence, x = —
x 2 2x + 2
x2 –14 –5x
4. (y + 4)2 = 9
x – 7 = 0 or x + 2 = 0 (y + 4)(y + 4) = 9
x = 7 x = –2 y2 + 4y + 4y + 16 = 9
Hence, x = 7 or x = –2. y2 + 8y + 7 = 0
(y + 7)(y + 1) = 0
y 7 7y
y 1 y +
y 2
7 8y
y + 7 = 0 or y + 1 = 0
Paper 2 y = −7 y = −1
Hence, y = −7 or y = −1.
1. p(p + 1) = 12
p2 + p = 12
p2 + p − 12 = 0 5. 2y2 = y + 36
(p + 4)(p − 3) = 0 2y − y − 36 = 0
2

p 4 4p (2y − 9)(y + 4) = 0
2y –9 –9y
p –3 –3p +
y 4 8y +
p2
–12 p
2y 2
–36 –y
p + 4 = 0 or p − 3 = 0
2y − 9 = 0 or y+4=0
p = −4 p = 3
2y = 9 y = −4
Hence, p = −4 or p = 3. 9
y = —
2
Hence, y = —9 or y = −4.
2

© Penerbitan Pelangi Sdn. Bhd. 4


 Mathematics  SPM  Chapter 11 

6. 2x2 − 3
x = ––––––– 9. 4k2 = 21 + 8k
5 4k2 − 8k − 21 = 0
5x = 2x2 − 3 (2k + 3)(2k − 7) = 0
0 = 2x2 − 3 − 5x
2k 3 6k
2x − 5x − 3 = 0
2

(2x + 1)(x − 3) = 0 2k –7 –14k +


2x 1 x 4k2 –21 –8k
x –3 –6x + 2k + 3 = 0 or 2k − 7 = 0
2x2 –3 –5x 2k = −3 2k = 7
3
k = − — 7
k = —
2x + 1 = 0 or x − 3 = 0 2 2
2x = −1 x = 3 3 or k = —7.
Hence, k = − —
x = − — 1 2 2
2
1 or x = 3.
Hence, x = − —
2 10. (2h + 1)(2h + 2) = 6
4h2 + 4h + 2h + 2 = 6
3 – 2k2 = k 4h2 + 6h + 2 − 6 = 0
7. ––––––– 4h2 + 6h − 4 = 0
5
3 − 2k2 = 5k 2h2 + 3h − 2 = 0
0 = 2k2 + 5k − 3 (2h − 1)(h + 2) = 0
2k + 5k − 3 = 0
2 2h –1 –h
(2k − 1)(k + 3) = 0 h 2 4h +
2k –1 –k 2h 2
–2 3h
k 3 6k + 2h − 1 = 0 or h+2=0
2k2 –3 5k 2h = 1 h = −2
h = — 1
2k − 1 = 0 or k + 3 = 0 2
2k = 1 k = −3 1 or h = −2.
1 Hence, h = —
k = — 2
2
1 or k = −3.
Hence, k = —
2 11. 2 + 9v − 2v2 = 4(1 + v)
2 + 9v − 2v2 = 4 + 4v
8. 5 − 23x = x + 5x2 0 = 4 + 4v − 2 − 9v + 2v2
0 = x + 5x2 − 5 + 23x 0 = 2v2 − 5v + 2
5x2 + 24x − 5 = 0 2v2 − 5v + 2 = 0
(5x − 1)(x + 5) = 0 (2v − 1)(v − 2) = 0

5x –1 –x 2v –1 –v

x 5 25x + v –2 –4v +

5x 2
–5 24x 2v2 +2 –5v

5x − 1 = 0 or x + 5 = 0 2v − 1 = 0 or v − 2 = 0
5x = 1 x = −5 2v = 1 v = 2
1 v =—1
x = — 2
5
1 or x = −5. 1 or v = 2.
Hence, v = —
Hence, x = —
5 2

5 © Penerbitan Pelangi Sdn. Bhd.


  Mathematics  SPM  Chapter 11

12. 5k + 2 = k2 15. (a) Area of square ABCD


––––––
3 = (m + 2)(m + 2)
5k + 2 = 3k2
0 = 3k2 − 5k − 2 (b) (m + 2)(m + 2) = 36
3k − 5k − 2 = 0
2 m2 + 2m + 2m + 4 = 36
(3k + 1)(k − 2) = 0 m2 + 4m + 4 − 36 = 0
m2 + 4m − 32 = 0
3k 1 k (m − 4)(m + 8) = 0
k –2 –6k +
m –4 –4m
3k 2
–2 –5k
m 8 8m +
3k + 1 = 0 or k − 2 = 0 m –32 4m2
3k = −1 k = 2
1 m − 4 = 0 or m + 8 = 0
k = − — m = 4 m = −8 (Impossible)
3
1 or k = 2.
Hence, k = − — Hence, m = 4.
3

16. (2t)2 + (2t − 1)2 = 52


13. 4m2 – 2 = 1
––––––– 4t2 + (2t − 1)(2t − 1) = 25
7m
4m2 − 2 = 7m 4t2 + (4t2 − 4t + 1) = 25
4m2 − 7m − 2 = 0 8t2 − 4t + 1 − 25 = 0
(4m + 1)(m − 2) = 0 8t2 − 4t − 24 = 0
2t2 − t − 6 = 0
4m 1 m (2t + 3)(t − 2) = 0
m –2 –8m + 2t 3 3t
4m2 –2 –7m t –2 –4t +
4m + 1 = 0 or m − 2 = 0 2t 2
–6 –t
4m = −1 m = 2 2t + 3 = 0 or t − 2 = 0
m = − — 1 3
4 t = − — (Impossible) t = 2
2
1 or m = 2.
Hence, m = – —
4 Hence, t = 2.

14. 2k = ––––– 2–k


3k
2k × 3k = 2 − k
6k2 = 2 − k
6k2 + k − 2 = 0
(3k + 2)(2k − 1) = 0
3k 2 4k
2k –1 –3k +
6k2 –2 k

3k + 2 = 0 or 2k − 1 = 0
3k = −2 2k = 1
k = − — 2 k = —1
3 2
2 1
Hence, k = − — or k = —.
3 2

© Penerbitan Pelangi Sdn. Bhd. 6